JEG SER DE BØGELYSE ØER – OG DETTE FOLK ER VORT: Om emotionalisering, subjektivering og danske sange - Damsholt, Tine (Tidsskriftet Antropologi, 2000)
The article deals with questions of subjectivation. The emotional bonds between a landscape and the individual as interpreted in Danish patriotic songs from the 19th-century are seen as crucial in the process of subjectivation turning the Danish population into a patriotic or selfconscious people. In the songs the sensing self is turned into a Danish self, an individual subject but part of a certain landscape, history and nation. Furthermore the Danish folkhigh-schools are seen as institutions of subject-ivation, since singing patriotic songs here became a natural part of everyday life. In the light of the Foucauldian perspective the emotional and bodily experiences at the folk-highschools (often staged outdoors in the Danish landscape) are interpreted as "technologies of the national self", since it is precisely via individuals’ work with themselves that the national subjectivation takes place.